2021
DOI: 10.1038/s41598-021-87897-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic potential of hypoxia-induced genes in liquid biopsies of breast cancer patients

Abstract: In tumor cells, higher expression of glucose transporter proteins (GLUT) and carbonic anhydrases (CAIX) genes is influenced by hypoxia-induced factors (HIF).Thus, we aimed to study the expression profile of these markers in sequential peripheral blood collections performed in breast cancer patients in order to verify their predictive potential in liquid biopsies. Gene expressions were analyzed by qPCR in tumor and blood samples from 125 patients and 25 healthy women. Differential expression was determined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The theoretical cell surface protein panel consisted of proteins associated with cell–cell junctions (GJA1 and RND1) and those that survive in hypoxic conditions (CA9, GLUT1, and SLC6A6). Studies have shown that CAIX is overexpressed in hypoxic tumors and may co-localize with GLUT1, a HIF1α-induced nutrient transporter that is being studied in liquid biopsies for certain types of breast cancer [ 9 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical cell surface protein panel consisted of proteins associated with cell–cell junctions (GJA1 and RND1) and those that survive in hypoxic conditions (CA9, GLUT1, and SLC6A6). Studies have shown that CAIX is overexpressed in hypoxic tumors and may co-localize with GLUT1, a HIF1α-induced nutrient transporter that is being studied in liquid biopsies for certain types of breast cancer [ 9 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given that studies have recently been conducted to evaluate CA9 expression in blood samples as a potential diagnostic marker for renal cell carcinoma [8] and breast cancer [9] with promising results, CA9 expression in blood samples may have potential as a diagnostic marker for primary duodenal carcinoma as well.…”
Section: Discussion/conclusionmentioning
confidence: 99%